Magnetic–Dielectric Synergy in One-Dimensional Metal Heterostructures for Enhanced Low-Frequency Microwave Absorption - Hu, Feiyue; Zhang, Peigen; Ding, Pei; Zhang, Shuo; Fan, Bingbing; Shamshirgar, Ali Saffar; Zheng, Wei; Sun, Wenwen; Cai, Longzhu; Xie, Haijiao; Shao, Qiyue; Rosen, Johanna; et al. (Nano-Micro Letters, 2026)
Microwave absorption (MA) materials often face poor synergy between impedance matching and attenuation in the low-frequency range. Balancing permittivity and permeability through magnetic–dielectric synergy is a promising strategy to address this issue. To realize the synergy, herein, Sn whiskers with an in situ oxide layer served as substrates for magnetic-loss-active CoNi nanosheet growth, forming a hierarchical CoNi@SnO2@Sn (CNS) heterostructure. The CNS absorber achieves a minimum reflection loss (RLmin) value of − 62.29 dB with an effective absorption bandwidth (EAB) of 2.2 GHz, covering the entire C-band with 70% absorption at only 2.61 mm thickness. The nanosheet design of CoNi enhances magnetic anisotropy to promote natural resonance, while the conductive Sn core and abundant Sn/SnO2 and CoNi/SnO2 heterointerfaces facilitate conduction loss and dielectric polarization. When composited into a thermoplastic polyurethane (TPU) matrix, the resulting CNS/TPU-2 film (20 wt% CNS) exhibits an RLmin value of -61.04 dB and a 2.5 GHz EAB. Its in-plane and through-plane thermal conductivities reach 2.41 and 0.51 W m−1 K−1, representing 4.1 and 2.6 times those of pure TPU films, respectively, facilitating heat dissipation from protected devices. This work provides valuable insights into magnetic–dielectric synergy for low-frequency MA of 1D metal-based materials, offering promising potential for 5G communications and flexible electronics. Highlights: 1 The hierarchical structure of CoNi nanosheets wrapped on one-dimensional Sn whiskers enhances magnetic anisotropy and dielectric losses, enabling strong magnetic–dielectric synergy. 2 The CoNi@SnO2@Sn (CNS) filler achieves − 62.29 dB reflection loss and 2.2 GHz bandwidth, fully covering the C-band with > 70% absorption, outperforming most low-frequency absorbers. 3 A flexible CNS/TPU film exhibits superior low-frequency microwave absorption and thermal conductivity, expanding its potential applications in communication electronics.